A cotton NAC domain transcription factor, GhFSN5, negatively regulates secondary cell wall biosynthesis and anther development in transgenic Arabidopsis - Sun, Qianwen (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.